Epidemiological behavior of health care in Factory Workers of a Brewing Company in the city of Lima, period 2004 to 2006. - Carrasco Villadoma, Cristian (2010)
Introduction: Little is known in Peru about the extent of workers exposure to occupational hazards, and we do not have a system with consistent and regular statistical information about diseases and accidents in the working place. We present the policy followed by a private company on this issue. Objective: The objective is to determine the epidemiological profile of conditions treated at the medical office in the aforementioned brewing company during a 20/month period (November 2004 to June 2006).   Material and method: The sample included 382 workers (100% of the factory workforce) and considered variables for a descriptive and retrospective cross-sectional observational analysis, since morbidity rates were calculated according to the frequency of conditions taken care of in the office. Afterwards, results were compared with similar studies with respect to common diseases, accidents, referrals and leaves of absence.   Results: The factory workforce is predominantly composed of young male subjects, their average age is 26 years, most of them (91.9%) are fit, and their most frequent medical conditions include upper respiratory diseases, digestive diseases, occupational diseases and industrial injuries (with a lower incidence compared to other studies, and most frequently found cases correspond to wounds in the hands), and musculoskeletal and joint conditions (being back pain the most frequent condition), and headache. When deemed necessary, workers were sent to the dental health office, and leaves of absence were issued in such cases.   Conclusions: This study focuses to a current problem in our country, where there is no reliable and verifiable records regarding health status of factory workers and the frequency of occupational diseases and injuries. Further studies and developmental activities are needed in order to improve occupational health in our country. Introduction: Little is known in Peru about the extent of workers exposure to occupational hazards, and we do not have a system with consistent and regular statistical information about diseases and accidents in the working place. We present the policy followed by a private company on this issue. Objective: The objective is to determine the epidemiological profile of conditions treated at the medical office in the aforementioned brewing company during a 20/month period (November 2004 to June 2006).   Material and method: The sample included 382 workers (100% of the factory workforce) and considered variables for a descriptive and retrospective cross-sectional observational analysis, since morbidity rates were calculated according to the frequency of conditions taken care of in the office. Afterwards, results were compared with similar studies with respect to common diseases, accidents, referrals and leaves of absence.   Results: The factory workforce is predominantly composed of young male subjects, their average age is 26 years, most of them (91.9%) are fit, and their most frequent medical conditions include upper respiratory diseases, digestive diseases, occupational diseases and industrial injuries (with a lower incidence compared to other studies, and most frequently found cases correspond to wounds in the hands), and musculoskeletal and joint conditions (being back pain the most frequent condition), and headache. When deemed necessary, workers were sent to the dental health office, and leaves of absence were issued in such cases.   Conclusions: This study focuses to a current problem in our country, where there is no reliable and verifiable records regarding health status of factory workers and the frequency of occupational diseases and injuries. Further studies and developmental activities are needed in order to improve occupational health in our country.